The complete mitochondrial genome of the Critically Endangered Saba Green Iguana, Iguana iguana (Squamata: Iguanidae) - Matthijs P. van den Burg; Ana Ramón-Laca; Albert Carné Constans; Adolphe O. Debrot; David R. Vieites (Mitochondrial DNA. Part B. Resources, 2023)
The populations of native iguanas in the Caribbean Lesser Antilles are threatened by the wide occurrence and spread of non-native iguanas. Until recently, competitive hybridization was not believed to threaten the Saba Green Iguana, a subpopulation of Iguana iguana (Linnaeus, 1758) from the island of Saba. However, the arrival of non-native iguanas has put the native population at risk, leading to a change in the conservation status of the Saba Green Iguana to Critically Endangered, according to guidelines from the International Union for the Conservation of Nature. Here, we generated the complete mitogenome of the Saba Green Iguana using Oxford Nanopore long-read technology. The mitogenome is 16,626 bp long and has 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region (1194 bp). Noteworthy, this is only the second published mitogenome for the Iguana iguana species complex, despite the known high intraspecific genetic variation.